Analysis and synthesis of positive systems under ℓ1 and L1 performance - Chen, Xiaoming (Springer, 2016)
This thesis introduces novel and significant results regarding the analysis and synthesis of positive systems, especially under l1 and L1 performance. It describes stability analysis, controller synthesis, and bounding positivity-preserving observer and filtering design for a variety of both discrete and continuous positive systems. It subsequently derives computationally efficient solutions based on linear programming in terms of matrix inequalities, as well as a number of analytical solutions obtained for special cases. The thesis applies a range of novel approaches and fundamental techniques to the further study of positive systems, thus contributing significantly to the theory of positive systems, a "hot topic" in the field of control. .
"Doctoral thesis accepted by The University of Hong Kong, Hong Kong."
Keywords: Positive systems.; elektronické knihy; electronic books